Surgical Outcome of Tumors of Spinal cord, Nerve roots, Meninges, and Vertebral column – Our Experience in Tertiary level Hospital - Soumen Samadder; Mithun Sardar; Kazi Hafiz Uddin; Misbah Uddin Ahmad; Md Motasimul Hasan; Shamsuzzaman Mondle; ATM Ashadullah; Md Joynul Islam (Bangladesh Journal of Neurosurgery, 2024)
Background: Spinal cord tumors can result in dramatic neurological and functional disabilities in the patients. We aimed to know the different types of spinal tumors and the correlation between clinical presentation and pathological findings and compare the outcomes of these tumors postoperatively. Methods: A total of 410 patients were included in the retrospective study group. The duration of the study was January 2016 to October 2022 (82 months). After a thorough clinical evaluation, patients were subjected to magnetic resonance imaging (MRI) and then surgery. They were described based on age, sex, location of the tumor, type of the tumor, symptoms, histopathological type, surgical resection, and complications. Results: The study included 229 (56%) males and 181 (44%) females and their ages ranged from 6 years to 74 years. Out of the 410 patients, 203(49.51%) had intradural extramedullary, 121(29.51%) had extradural and 86(20.98%) had intradural intramedullary spinal tumors. A predilection towards the thoracic region (39.50%) and cervical region (28.40%). Lumbar region (20.10%) and Sacral region (4.10%), Cervicodorsal region (1.40%), Dorsolumbar region (3.00%), and Craniovertebral junction (3.50%) were seen. The tumors were excised completely in 72.68% of the patients while neartotal resection was done in 17.82%, subtotal resection in 7.32%, and only biopsy in 2.2% of patients. Histopathologically most of the tumors were Schwannoma (38.78%), then Meningioma (11.71%), Ependymoma (11.70%), Astrocytoma (10.98%), and others were found. There was significant improvement (33.66%) in the modified McCormicks score at discharge follow-up. Conclusions: Intradural extramedullary is the most common spinal cord tumor. The majority of the cases presented with sensorimotor symptoms and pain is the predominant clinical complaint. Spinal cord tumors are most commonly observed in the 2nd to 4th decade of life with a gradual decline in the incidence towards the extremes of age group. Surgery is the definitive treatment and the aim of the surgery is gross total resection Bang. J Neurosurgery 2024; 13(2): 112-120